Project Contract Management and Performance of Water Project in Baringo County, Kenya - Openji, Sylus; Osoro, Anthony (International Journal of Supply Chain Management, 2024)
Purpose: This study sought to explore on projects contract management and performance of water contract in Baringo County, Kenya. The specific objectives of the study were: To determine the effect of project planning, community participation, project implementation and project evaluation on performance of contracts in Baringo County, Kenya. Methodology: The study adopts a descriptive research design, and used both qualitative and quantitative approaches. The target population was200 respondent from water projects management in Baringo County. This study used purposive random sampling techniques. It will be census survey. The study used open-ended and closed-ended questionnaire as the main mode of data collection. Primary data was collected using structured questionnaires. Secondary data was collected from institutional documents, Ministry of water publications within the County and relevant publications in referred journals. The collected data was edited, coded and entered into Statistical Package for Social Science version 26. Data was analysed using descriptive and inferential statistics. In particular, Regression Analysis was used to investigate the relationships between hypothesized variables. Analysis of Variance (ANOVA) was also be used to investigate whether independent variables has a combined effect on the dependent variable. The data was analysed through the use of descriptive statistics. ANOVA, t-test, Pearson correlation, p- values and coefficient of determination was used in the data analysis. The analysis from cropha alpha was acceptable for reliability and validity with a results of over 0.7 and 0.5 respectively. Data was presented in form of tables. Findings: The study summary agrees that there is a strong relationship between the independent and dependent variable. Also the conclusion and recommendation of this study confirms that there is need to implement the findings of this study. Unique Contribution to Theory, Practice and Policy: The theories on which the study is hinged are contingency theory, the principal-agent theory, social cognitive theory and the CBPR model. The study recommends and on firms that the implementation of contracts practice and performance of water contracts in eastern region, Kenya was significant relationship. That in future different counties needs to strengthen performance of water contracts Baringo County in Kenya and procurement process to all counties in Kenya, with the help of Project planning, community participation Project implementation and Tracking stock.